WORKSHOP KREATIVITAS VISUAL DAN PELATIHAN TRANSFORMASI BISNIS UMKM MAJALENGKA: MENGGALI TREN TERBARU DENGAN DESAIN CANVA, E-COMMERCE SHOPEE, DAN TIKTOK - Syamsul Arif Billah; Ajeng Ayu Wulandari, Adi Junaedi (Adiba Aisha Amira, 2023)
In the rapidly evolving digital era, Micro, Small, and Medium Enterprises (MSMEs) in Majalengka face various challenges and opportunities to adapt to the dynamic market changes. The